Effect of Pre-Sowing Treatments on Seed Germination and Seedling Vigour Index of Juniperus polycarpos C. Koch - Negi, P. S.; Sharma, Sandeep (Indian Forester, 2017)
Juniperus polycarpos C. Koch is an important conifer of dry temperate and cold desert region of Western Himalaya. The seeds were given different pre-sowing treatments viz., soaking in different concentration of citric acid ranging from 4000ppm to 12000ppm for 4 period, cold moist stratification in cowdung, sand and goat dung for different time period ranging from 45 days to 60 days to study their effect on its germination and seedling vigour index. Significant differences were observed in germination percentage and seedling vigour treated with different pre-sowing treatments. Seeds treated with cowdung and placed in open pits for 60 days period for cold moist stratification treatment during winter recorded maximum 70.00 per cent germination which was followed by treatment i.e., soaking in citric acid 8000 ppm for 4 days period with 62.66 per cent germination where as untreated seeds (control) recorded minimum 40 per cent germination. Similarly, seeds treated with cowdung and placed in open pits for 60 days period during winter recorded maximum seedling vigour index (189.74) where as minimum seedling vigour index (55.20) was recorded in seeds treated with goat dung and placed in open pits for 60 days period for cold moist stratification during winter. Therefore, it is recommended that the seeds of Juniperus polycarpos should be treated with pre-sowing treatment i.e., cold moist stratification in cowdung placed in open pits for 60 days period during winter before sowing in the nursery for breaking seed dormancy and getting maximum germination. The best treatment registered a 75.00 per cent increase in germination per cent over control.